“Demographic Winter”: Does it Have an Impact on Indonesia? Population Economic Records - Rosyadi Rosyadi; Tri Cicik Wijayanti; Jiuhardi Jiuhardi (ETIKONOMI, 2023)
The originality of this paper focuses on existing material. It has implications for uncovering Indonesia's barriers to population growth, which are associated with economic components such as employment, wages, and happiness. On this basis, the orientation of this study is centered on cycles in the "demographic winter" of Indonesia. Short-term data for 2016–2021 is applied. This research is using multiple regression. In its actualization, population composition has a positive effect on the aging population, the aging population has a positive effect on the young workforce, and the young workforce affects wages. Another direct effect found a positive effect between fertility on marriage and birth productivity. From other moments, it is evident that being married positively affects birth productivity, and life expectancy and birth productivity positively affect happiness. In theoretical construction, the findings suggest further identification beyond the existing premise. The research in the next edition is growing by including other non-economic factors such as health, migration, mortality, and education.JEL Classification: C12, C22, J10, J21, I31How to Cite:Rosyadi, R., Wijayanti, T. C., & Jiuhardi, J. (2023). “Demographic Winter”: Does it Have an Impact on Indonesia? Population Economic Records. Etikonomi, 22(2), 389 – 408. https://doi.org/10.15408/etk.v22i2.31264.